Auditors’ Quantitative Materiality Judgments: Properties and Implications for Financial Reporting Reliability - CHOUDHARY, PREETI; MERKLEY, KENNETH; SCHIPPER, KATHERINE (Journal of Accounting Research, 2019)
ABSTRACT We analyze data made available through the PCAOB (Public Company Accounting Oversight Board) to provide descriptive evidence on the properties of auditors’ actual quantitative materiality judgments and the implications of those judgments for financial reporting. Auditors’ quantitative materiality judgments do not appear to result simply from applying conventional rules of thumb (e.g., 5% of pretax income), but instead are associated with size‐related financial statement outcomes (income, revenues, and assets), where the relative importance of the size‐related outcomes varies with client characteristics such as financial performance. Using the distribution of actual materiality amounts reported by auditors to the PCAOB as part of the audit‐inspection process, we construct a materiality‐judgment measure that locates a specific materiality amount within a normal range that is both comparable across varying client characteristics and supported by guidance in audit firm internal policy manuals. We find that looser materiality (an amount closer to the high end of a normal materiality range) is associated with fewer audit hours and lower audit fees, supporting the construct validity of this measure. We also find that looser materiality is associated with lower amounts of proposed audit adjustments and, in extreme cases, with a greater incidence of restatements, highlighting the importance of auditor materiality assessments for financial reporting reliability.